Avaliação da atividade fotoprotetora, antioxidante e variação sazonal do extrato padronizado de Mentha x villosa - Gomes, Juliana de Medeiros (2022)
Topical sunscreens can consist of chemical and/or physical filters, and antioxidant compounds, aiming at a broader protection. However, this protection is often lacking and, therefore, an interesting strategy is the addition of natural compounds or plant extracts rich in polyphenols in these formulations, since they can present antioxidant and photoprotective activity. Within this context, Lamiaceae Family becomes quite interesting, since it is the main plant family used in the cosmetic industry and has members with a large amount of phenolic compounds. Thus, Mentha x villosa has been studied in photoprotection, since its a species of easy cultivation and presents as main non-volatile compounds, rosmarinic acid (RA) and flavonoids. Thus, this work aimed to continue evaluating the photoprotective activity of M. x villosa through the seasonal study of the sun protection factor (SPF), antioxidant activity, phenolic, flavonoid and RA content, and also evaluating whether UV radiation and precipitation could influence the production of these metabolites. Subsequently, optimization of the extraction of polyphenols and RA was carried out through the use of a factorial design, varying the percentage of ethanol and powder/solvent ratio used. After optimization, principal component analysis (PCA), LC-HRMS and dereplication (MSn) of the extract were performed in order to identify the compounds present in M. x villosa and understand which substances had their extraction favored. Then, SPF, UVA protection factor (UVA-FP) and critical wavelength were determined. These tests were made from the preparation of 8 different formulations containing the optimized extract. Antioxidant activity was evaluated by performing scavenging DPPH and ABTS radicais assays. As a result, it was seen that the best month for harvest of M. x villosa was September and that higher concentrations of polyphenols and flavonoids favor the increase of SPF, as well as, the concentration of RA directly influences antioxidant activity of the species. In addition, it was observed that solar radiation influences on the production of phenolics and the increase in SPF, while precipitation does not seem to influence parameters studied. Regarding the extraction optimization, it was seen that the best conditions for the joint extraction of polyphenols and RA were 70% ethanol and powder/solvent ratio at 5%, promoting the attainment of 264.58 mg GAE/g and 101.96 mg/ g of total phenolics and RA content, respectively. PCA revealed that 7 major components contributed to differentiating the samples and, based on LC-MS analysis, these compounds were identified as polyphenols, along with 23 other compounds. Regarding antioxidant activity, optimized extract showed EC50 = 42.44 μg/mL in the DPPH radical inhibition assay and EC50 = 322.87 μg/mL in the ABTS radical assay. In the evaluation of photoprotective activity, formulations 5 and 6 produced for these tests presented the best values of SPF (23.20 and 30.63) and UVA-PF (12.25 and 26.53), respectively. Thus, corroborating all the results obtained, this work demonstrated the great photoprotective potential of M. x villosa, which was able to provide important broad-spectrum protection against UVA and UVB rays, associated with antioxidant activity and also, reducing the concentration of chemical filter used in the formulation, suggesting an alternative to a safer product.